The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1063/1.476345
|View full text |Cite
|
Sign up to set email alerts
|

Cluster velocity distributions in a vapor at equilibrium

Abstract: We present the microscopic description of the vapor using the concept of cluster. Taking into consideration nonideal contributions, the distribution functions of every cluster species are obtained. From these distribution functions it is possible to derive kinetic “temperatures” associated with each cluster species and it is shown that the internal kinetic temperature and the kinetic temperature associated with the center of mass of the clusters are different from the thermodynamic temperature of the system as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…We add a maximum connectivity distance d to the criteria to avoid unrealistic bonding. Two particles separated by a distance greater than this maximum distance are considered as non-bonded even if their relative velocity is by chance zero [16]. We show that the velocity average introduces an important overestimation on the predicted percolation density at all temperatures.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We add a maximum connectivity distance d to the criteria to avoid unrealistic bonding. Two particles separated by a distance greater than this maximum distance are considered as non-bonded even if their relative velocity is by chance zero [16]. We show that the velocity average introduces an important overestimation on the predicted percolation density at all temperatures.…”
Section: Introductionmentioning
confidence: 92%
“…More recently, Hill's criterion has been reconsidered in molecular dynamics studies of small clusters [15,16] and the critical percolation behaviour of Lennard-Jones fluids [17]. It has been suggested that the percolation line − the line that separates the temperature-density phase space into percolated and non-percolated states − might be experimentally observable [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…22 One can also require that, besides proximity, the particles satisfy some energy requirement associated to the idea of forming a bound state. 23,24 These energetic clusters were proposed as better candidates to have a dynamic theory of vapors, but they have nonclassical kinetic properties. For example, at equilibrium their velocity distribution function is not Maxwellian.…”
Section: ͔mentioning
confidence: 99%
“…23 The kinetic origin of memory effects come from dealing with clusters simply classified by their size without taking into consideration quite different dynamic characteristics ͑such as angular momentum or internal energy͒ between them. To have local equations, the clusters must be classified according to the values of their degrees of freedom, requiring a kinetic approach by means of kinetic equations.…”
Section: Transition Ratesmentioning
confidence: 99%
“…27 It should be mentioned that the HE criterion has been considered in MD studies of small clusters and the critical percolation behavior of Lennard-Jones fluids by several authors. 28,29,30 It has been suggested that the percolation line-the line that separates the temperature-density phase diagram into percolated and non-percolated states-might be experimentally observable. 30,31 Moreover, cluster analysis based on this criterion seems to be useful in locating the gas-liquid coexistence curve.…”
Section: Introductionmentioning
confidence: 99%